Decentralized planning for non-communicable diseases: protocol for an explanatory study of local self-government projects in Kerala, India - Sujatha, Chintha; Kannan, Srinivasan (International Journal Of Community Medicine And Public Health, 2024)
Background: Priority setting and resource allocation in decentralised planning is often not in line with the social and economic burden associated with non-communicable diseases (NCD). This is a protocol developed for the purpose of analysing the pattern of budgetary allocation and utilisation of funds for health sector projects on non-communicable diseases by the local self-government (LSG) institutions in Kerala. It is also proposed to document the processes along with the stakeholders’ role in planning. Methods: Following explanatory design, first we will do secondary data analysis of health sector projects on NCD fund allocation and utilisation, followed by document analysis and key informant interviews in LSGs at selected districts of Kerala. Following policy framework used in public health related policy processes, will perform descriptive analysis, based on stages heuristic in decentralised planning. Multiple dimensions of priority setting and allocation process will be studied. Explanatory analysis for resource allocation process will be studied using Kingdon’s multiple streams framework. Conclusions: The study will help in understanding the decision-making process for fund allocation with the specific focus on NCD. It will also help in building an evidenced based framework for decentralized health planning. Trial Registration: No: SCT/IEC/1849/FEBRUARY/2022.